La politique agricole et l’accumulation du capital : Le cas des États-Unis - Perelman, Michael (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1981)
Confronted with economic crisis, american agricultural policy since 1970 has been dominated by one priority : the solution of problems associated with other sectors, by saving public agricultural expenses as well as by using exports as a « food weapon ». But this policy does no more than shift the contradictions of american society : it doesn't stop the food/wage spiral and it re-activates the internal tensions of agricultural production. A longer term logic dominates this short term policy: to safeguard the functions of agriculture within the accumulation process. The study emphasizes the function of supplier of labor for other sectors of agriculture. It shows how the american food model, by consuming an irrational amount of ressources, ensures that the labor's supply grows more rapidly than its demande.